2012
DOI: 10.1371/journal.pone.0035107
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Acidification and the Loss of Phenolic Substances in Marine Plants

Abstract: Rising atmospheric CO2 often triggers the production of plant phenolics, including many that serve as herbivore deterrents, digestion reducers, antimicrobials, or ultraviolet sunscreens. Such responses are predicted by popular models of plant defense, especially resource availability models which link carbon availability to phenolic biosynthesis. CO2 availability is also increasing in the oceans, where anthropogenic emissions cause ocean acidification, decreasing seawater pH and shifting the carbonate system t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
127
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 161 publications
(138 citation statements)
references
References 54 publications
10
127
1
Order By: Relevance
“…We found that upper photic zone coccolithophore communities in southern Tyrrhenian Sea water and Levante Bay were very similar in areas unaffected by elevated CO 2 . Future studies could combine in situ mesocosm-type experiments to constrain the movement of plankton at the seeps or use Free Ocean Carbon Experiments to control the CO 2 dose (Arnold et al, 2012). Given the shallow nature of the seeps, such work could also incorporate investigations of the possible effects of ultraviolet radiation.…”
Section: Discussionmentioning
confidence: 99%
“…We found that upper photic zone coccolithophore communities in southern Tyrrhenian Sea water and Levante Bay were very similar in areas unaffected by elevated CO 2 . Future studies could combine in situ mesocosm-type experiments to constrain the movement of plankton at the seeps or use Free Ocean Carbon Experiments to control the CO 2 dose (Arnold et al, 2012). Given the shallow nature of the seeps, such work could also incorporate investigations of the possible effects of ultraviolet radiation.…”
Section: Discussionmentioning
confidence: 99%
“…To date, in situ responses of marine organism to dissolved CO 2 increase are based on observations made near volcanic vents (Hall-Spencer et al 2008, Martin et al 2008, Porzio et al 2011, Johnson et al 2012. Recently, different techniques of in situ CO 2 manipulation, such as the Coral−Proto Free Ocean Carbon Enrichment System (Kline et al 2012), the Free Ocean Carbon Enrichment System (Arnold et al 2012), and the Carbon-Enriched Open Chamber System (Campbell & Fourqurean 2011) have been proposed. The development of new CO 2 in situ experiments can provide new insights and give straightforward answers or at least provide a piece of the puzzle about the effect of OA on macroalgae.…”
Section: Introductionmentioning
confidence: 99%
“…High CO 2 /low pH conditions cause the loss of antimicrobial phenolics in many seagrass species (Arnold et al 2012;Arnold et al 2014; but see Martínez-Crego et al 2014; Figure 1 sites (i), (j)). Phenolic acids known to inhibit the growth of the seagrass wasting disease pathogen, Layrinthula spp., were reduced by as much as~95% under "acidified" conditions.…”
Section: Coastal Zone Acidificationmentioning
confidence: 99%